Analisis Performa Sepeda Motor Sport 155cc 2 Tak dengan Beragam Jenis Bahan Bakar - Kurnia Rizky Nasution; Jufrizal Jufrizal; Supriatno Supriatno (CV. IRA PUBLISHING, 2025)
The development of two-wheeled automotive technology continues to advance, especially in fuel efficiency, engine performance, and emissions. One key factor affecting engine performance is fuel quality. This study investigates the effect of fuel octane rating on torque and power in a 155cc 2-stroke sport motorcycle at 3500–8000 rpm. Three fuel types were tested: Pertamax, Pertamax Turbo, and Pertalite. Maximum torque was recorded at 6000 rpm with values of 11.3 Nm (Pertamax), 11.8 Nm (Pertamax Turbo), and 11.6 Nm (Pertalite). Maximum power was observed at 8000 rpm with 8.2 kW, 8.6 kW, and 8.3 kW, respectively. In addition to octane rating, compression ratio, and engine speed significantly influence torque and power output.